2016
DOI: 10.1111/poms.12542
|View full text |Cite
|
Sign up to set email alerts
|

Duality Approaches to Economic Lot‐Sizing Games

Abstract: We consider the economic lot-sizing (ELS) game with general concave ordering cost.In this cooperative game, multiple retailers form a coalition by placing joint orders to a single supplier in order to reduce ordering cost. When both the inventory holding cost and backlogging cost are linear functions, it can be shown that the core of this game is non-empty. The main contribution of this paper is to show that a core allocation can be computed in polynomial time.Our approach is based on linear programming (LP) d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 41 publications
(90 reference statements)
0
16
0
Order By: Relevance
“…for some τ ≥ r, we can model the economic lot sizing problem for coalition R ⊆ N with the following linear program (Chen and Zhang 2006):…”
Section: The Economic Lot Sizing Gamementioning
confidence: 99%
See 3 more Smart Citations
“…for some τ ≥ r, we can model the economic lot sizing problem for coalition R ⊆ N with the following linear program (Chen and Zhang 2006):…”
Section: The Economic Lot Sizing Gamementioning
confidence: 99%
“…, k, for all j, k such that τ ≤ j ≤ k ≤ T . Although the decision variables are continuous, this interpretation is well-defined: Chen and Zhang (2006) showed that there always exists an optimal solution to (1) such that x jk ∈ {0, 1} for all j, k. The first term of the objective (1a) is the cost of greedily using the initial inventoryŝ r−1 R to satisfy demand in periods r, . .…”
Section: The Economic Lot Sizing Gamementioning
confidence: 99%
See 2 more Smart Citations
“…This is one of the central themes in cooperative game theory, which has wide applications. See, for example, facility location games (Goemans andSkutella 2000, Mallozzi 2011), inventory games (Anily and Haviv 2007, Chen 2009, Zhang 2009, Chen and Zhang 2016, and outsourcing games (Aydinliyim andVairaktarakis 2010, Cai andVairaktarakis 2012), to name a few. The set of such cost allocations is known as the core of a cooperative game (Shapley and Shubik 1969).…”
Section: Introductionmentioning
confidence: 99%